Store Atmosphere dan Gaya Hidup Hedonis sebagai Penentu Keputusan Pembelian (Studi pada Konsumen Rolag Kopi Kayoon Surabaya) - Kartika Ayu Wulandari; Sri Setyo Iriani (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2020)
The potential of cafÃ© and restaurant business in East Java is on the rise and remains enormous enough to run. This has triggered intense competition among cafÃ© business owners in Surabaya. Currently, there has been a change in lifestyle during society. People (specifically teenagers) in big cities prefer to spend their leisure to relax in the cafe. Many cafes have sprung up with distinguishing concepts to attract consumers. Rolag Kopi Kayoon Surabaya is one of the cafes that has carried out a marketing strategy by creating a different store atmosphere. The hedonic lifestyle of urban communities can be also one of the factors which influence the consumer purchasing decision. This study aims to analyze and discuss the effect of store atmosphere and hedonic lifestyle on purchasing decisions on consumers Rolag Kopi Kayoon Surabaya. This research was conducted at Rolag Kopi Kayoon Surabaya by using data of a questionnaire of 110 respondents with a minimum age of 17 years old. The sampling method used is a judgmental sampling. The measurement scale applied is the Likert scale. The statistical analysis used is multiple linear regression equation models. The results showed that the store atmosphere and hedonic lifestyle variables significantly and positively influenced purchasing decisions. The biggest influence on purchasing decisions is the store atmosphere with a level of influence at 20.7%.